Imagining an Institutionalised Social Dialogue in the South African Local Government-Led Development Landscape. Issue 1 (2nd January 2018) - Khambule, Isaac
Abstract: The world, because of globalisation and the recent economic crisis, has entered an era that recognises the importance of the participation of all stakeholders in economic development matters. This era is accompanied by a decentralisation process that led to an emphasis on participatory approaches to development issues at the local level. However, no participatory approach has been recognised as the most appropriate mechanism for development forums. In the midst of this, social dialogue is proposed as such a participatory approach that can integrate the public, private, businesses and financial institutions in the bid to create effective responses to immediate developmental challenges. The article established that South Africa is still struggling to create efficient economic development planning structures that can address the key failings of local economic development (LED). This article imagines the utilisation of an institutionalised social dialogue in the South African local government-led development space as an antidote to current failures of LED and disparities between the public, private and civil society. Local Economic Development Agencies (LEDAs) can therefore be imagined as appropriate social dialogue structures that can mitigate the current failures of LED through integrating different capacities and resources from local stakeholders. This article therefore recommends the institutionalisation of social dialogue through LEDAs as the collaborative economic development planning agency at the local government-led development landscape.